HUBUNGAN PERATURAN DI SEKOLAH DAN PENGARUH TEMAN DENGAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) - Friska Realita; Noveri Aisyaroh (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2020)
Schools introduce the health to students, it should not be too difficult because each school have a School Health Enterprise (UKS). The Clean and Healthy Behaviour (PHBS) is the spearhead for health development in order to improve people's healthy living behavior. PHBS efforts if not carried out by each family and family members will be a risk factor for disease, both infectious or non-communicable diseases. How to apply the PHBS indicator at the household level, at school, at work, in public places and other places, of course depends very much on the awareness and active participation of the community in their respective neighborhoods. The population is students of Sultan Agung Semarang Islamic Junior High School. There are 13 classes with different number of its students, so sample size is determined by proportional stratified random sampling so that they can represent each class. The data is obtained by filling out the questionnaires and observed by checklist.. The results of the study showed that respondents stated that they followed the rules of the school as many as 60 respondents or 75%. Most respondents in doing PHBS were influenced by friends as many as 53 respondents or 66.22%. Conclusion is there are no relationship between the regulations and influence of friends with PHBS behavior